Թարգմանությունը որպես բնագրի ընկալման, իմաստի հաղորդման և միջմշակութային հաղորդակցման միջոց - Սեդա Գաբրիելյան (ՀՀ ԳԱԱ հրատ.)
Современное переводоведение можно охарактеризовать как результат междисциплинарных исследований, использующих методы целого ряда наук.Translation Studies being interdisciplinary by their essence lead to scientific research methods of many branches necessitating the consideration of different factors.
Keywords: Language and Literature; Translation and interpretation